2014
DOI: 10.1088/1674-1056/23/9/097504
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetic simulation of Sm—Co/α-Fe/Sm—Co trilayers with various angles between easy axes and the film plane

Abstract: Zhang Xi-Chao(张溪超) a) , Zhao Guo-Ping(赵国平) a) † , Xia Jing(夏 静) a) , Yue Ming(岳 明) b) , Yuan Xin-Hong(袁新红) a) , and Xie Lin-Hua(谢林华) a) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Systematically, the effects of the dipolar interaction on magnetic properties and magnetization processes in array of Co nanowires are investigated using OOMMF micromagnetic simulations. [18][19][20] These simulations are performed with an algorithm-based finite difference method. Equilibrium structures of the magnetization are characterized by local energy minima.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematically, the effects of the dipolar interaction on magnetic properties and magnetization processes in array of Co nanowires are investigated using OOMMF micromagnetic simulations. [18][19][20] These simulations are performed with an algorithm-based finite difference method. Equilibrium structures of the magnetization are characterized by local energy minima.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the saturation magnetization and exchange stiffness are very close to those of corresponding bulk materials in nanowire array when the diameter increases up to 10 nm. The material parameters are as follows: [14,19] saturation magnetization M s = 17.86 kGs, crystalline anisotropy constant K 1 = 0.54 × 10 7 erg•cm −3 , and exchange constant A = 20 × 10 −7 erg•cm −1 . In this paper, higher order terms of the magnetocrystalline anisotropy are ignored for simplicity, which makes the squareness of each hysteresis loop rectangular.…”
Section: Methodsmentioning
confidence: 99%
“…When t = 5 nm, the coercivity reaches the largest value of 5.975 T. Then the coercivity decreases rapidly while t ranges from 5 nm to 8 nm. In theoretical reports on the hard/soft exchange spring system, [28][29][30][31][32] it has been found that when the thickness of the hard layer is larger than its domain wall width, the reversal magnetization process is not sensitive to the specific value of the hard layer. As for our work in this paper, it is assumed that the optimum shell thickness, t = 5 nm, might also be related to the domain wall width.…”
Section: Effect Of Shell Thicknessmentioning
confidence: 99%
“…The fabrication of nanocrystalline composites is an effective method to obtain both high coercivity and high saturation magnetization, which could obtain high magnetic energy products through the exchange coupling of hard–soft magnetic phases [ 12 , 13 , 14 , 15 ]. Fe-Co alloy is an excellent soft magnetic material that has a high saturation magnetic moment and initial permeability [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%